The Mediating Effect Of Job Satisfaction And Organizational Commitment On Employee Turnover - Beny Tamrin; Alip Hanoky (Universitas Hamzanwadi, 2023)
This study aims to examine and analyse the mediating effect of job satisfaction and organizational commitment between link talent management on employee turnover in PT Kalimantan Sawit Kusuma Pontianak. This study focuses on human resource management with participants of this study were all 105 permanent employees. This study utilized census technique sampling because the total permanent employee only 105 employees. This research used a quantitative approach to test the hypotheses and explain the impact among variables. This study used path analysis to examine the role of mediation and the data were analysed using SPSS 24. Classical assumptions have been tested, to fulfil the requirements for the use of path analysis. The results of this study show that job satisfaction and organizational commitment have a significant mediating role in influencing the relationship between talent management and employee turnover. However, talent management, job satisfaction and commitment have a significant and negative influence on employee turnover.